2024
DOI: 10.1186/s12877-024-04772-1
|View full text |Cite
|
Sign up to set email alerts
|

Brain activation during standing balance control in dual-task paradigm and its correlation among older adults with mild cognitive impairment: a fNIRS study

Guocai Xu,
Mian Zhou,
Yan Chen
et al.

Abstract: Background This study aimed to compare the balance ability and functional brain oxygenation in the prefrontal cortex (PFC) among older adults with mild cognitive impairment (MCI) under single and dual tasks, and also investigate their relationship. Neural regulatory mechanisms of the brain in the MCI were shed light on in balance control conditions. Methods 21 older adults with MCI (female = 12, age: 71.19 ± 3.36 years) were recruited as the experi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Improvement in dynamic balance is not achieved simply by increasing the force output; instead, it involves the integration of different sensory systems, including visual, vestibular, and proprioceptive sensations [ 39 ]. Meanwhile, the central control of postural stability involves multiple cortical brain regions or networks, including the prefrontal-basal ganglia and sensorimotor networks [ 40 , 41 ]. Previous studies on cortico-muscular coupling and cortical activity have confirmed the complexity of the intrinsic physiological mechanisms underlying human postural control [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Improvement in dynamic balance is not achieved simply by increasing the force output; instead, it involves the integration of different sensory systems, including visual, vestibular, and proprioceptive sensations [ 39 ]. Meanwhile, the central control of postural stability involves multiple cortical brain regions or networks, including the prefrontal-basal ganglia and sensorimotor networks [ 40 , 41 ]. Previous studies on cortico-muscular coupling and cortical activity have confirmed the complexity of the intrinsic physiological mechanisms underlying human postural control [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%